Role of LDH levels in differentiating anemias - Zaidi, Noorin; Usmani, Rasha Zia; Tiwari, Kshama; Irfan, Sumaiya; Mehdi, Syed Riaz (Asian Journal of Medical Sciences, 2021)
Background: There is a need to differentiate megaloblastic anemia from mixed deficiency anemia as both require different management protocols. With the acquisition of more information about them, tests such as serum vitamin estimation and Schilling test, were found to have their limitations. Hence there is a need to search newer diagnostic candidates to differentiate between megaloblastic anemia and mixed deficiency anemia. Aims and Objective: The current study was undertaken to find usefulness of serum Lactate Dehydrogenase (LDH) in differentiating megaloblastic anemia from mixed deficiency anemia. Materials and Methods: 100 patients were included in the study. Blood smears were stained and analysed. Complete blood counts were performed. Bone marrow examination was done, where needed. Biochemical tests were performed for estimation of vitamin B12, Folate and for LDH. Results: Out of the 100 cases 51 were diagnosed as megaloblastic anemia and 49 were diagnosed as mixed deficiency anemia. The LDH levels were significantly higher in cases of megaloblastic anemia as compared to mixed deficiency anemia. Conclusion: Serum LDH levels can be used in differentiating megaloblastic anemia from mixed deficiency anemia.